Experimental Study on Optimal Design of Permeable Concrete Mix Ratio - WANG Baoqiang; LIAO Fangzhen (Renmin Zhujiang)
This experiment aimed to develop a new type of permeable concrete with high strength,with various mix ratio designs tried.In addition,the effects of various mix ratio designs on the compressive strength and permeability performance of permeable concrete were studied,and the optimization design scheme of the optimal aggregate and mix ratio of permeable concrete was proposed.The study shows that in permeable concrete,the high-efficiency water-reducing agent is effective in assisting silica fume dispersion;the use of mechanism sand can improve the compressive strength of permeable concrete;after adding fine aggregate and admixture,the optimal water-cement ratio is 0.32;the compressive strength after 28 d is improved,and the permeability is greater than 2 mm/s;when the structural strength requirement of permeable concrete pavement is not high,or when there is special concern about pavement clogging in a longer period of use,a higher water-cement ratio of 0.36 can be used.